Perancangan Interior Hydroterapi dan Fisioterapi di Surabaya - Olivia Fransisca Saputra; Hedy Constancia Indrani (Intra, 2017)
Hydrotherapy and physiotherapy are therapies that are truly required by the society, particularly those who are experiencing health problems. However, in Surabaya, the places that can accommodate such therapies are still insignificant. Hydrotherapy and physiotherapy can help people to move their body parts and perform their daily activities optimally. Activities involving hydrotherapy and physiotherapy require a conducive environment with a spatial design that support therapists in performing their therapeutic skills. The design of these spaces also need to be attractive in terms of aesthetics while also providing a sense of comfort for their users. This thesis aims to design the interior of a hydrotherapy and physiotherapy center in order to assist the society in performing their daily activities. It is designed with complete facilities consisting of medical rehabilitation spaces involving hydrotherapy and physiotherapy and providing doctors to support the therapeutic processes. The project uses the comparative design methodology, involving similar case studies and exploration so that the final design may articulate the facilities that are needed by the users according the design standards of places that accommodate hydrotherapy and physiotherapy.